2014
DOI: 10.1159/000356272
|View full text |Cite
|
Sign up to set email alerts
|

Degarelix versus Goserelin plus Bicalutamide Therapy for Lower Urinary Tract Symptom Relief, Prostate Volume Reduction and Quality of Life Improvement in Men with Prostate Cancer: A Systematic Review and Meta-Analysis

Abstract: Objective: We performed a systematic review and meta-analysis to assess the efficacy and tolerability of degarelix for lower urinary tract symptom relief, prostate volume reduction and quality of life improvement in men with prostate cancer (PCa). Materials and Methods: A literature review was performed to identify all of the published randomized controlled trials (RCTs) that used degarelix versus gonadotropin-releasing hormone agonists plus antiandrogens therapy for the treatment of PCa. The search included t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…This study was consistent with previous reports of the beneficial effects of goserelin on LUTS . However, in another study, reductions in IPSS were greater in patients treated with the GnRH antagonist degarelix than in those receiving the combination of goserelin and bicalutamide . Recent non‐interventional studies have suggested an improvement in LUTS induced by triptorelin, as measured by the IPSS .…”
Section: Discussionsupporting
confidence: 91%
“…This study was consistent with previous reports of the beneficial effects of goserelin on LUTS . However, in another study, reductions in IPSS were greater in patients treated with the GnRH antagonist degarelix than in those receiving the combination of goserelin and bicalutamide . Recent non‐interventional studies have suggested an improvement in LUTS induced by triptorelin, as measured by the IPSS .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the GnRH antagonist degarelix had a greater impact on LUTS at 12 weeks compared with the GnRH agonist goserelin, despite similar effects on PSA and testosterone suppression, which may suggest the mechanism on LUTS is independent of these markers Anderson et al 2013;Mason et al 2013;Cui et al 2014]. Although prostate volume was not measured in this observational study, there was a clear correlation between PSA suppression and LUTS improvement in this large cohort of patients.…”
Section: Discussionmentioning
confidence: 70%
“…In the past years, numerous studies have been carried out to identify risk factors associated with the etiology and pathogenesis of BPH [10,12,19,20]. Rohrmann et al [12] aimed to identify the relationship between smoking and BPH, but there was no statistical association.…”
Section: Discussionmentioning
confidence: 99%
“…Age, genetic, and hormonal factors have been traditionally considered as the main risk factors for BPH and its associated pathophysiology, but lifestyle elements such as PA, leisure, exercise, smoking, and drinking are now considered to play an important role in the development of BPH [10,11,12,13]. The importance of PA in the prevention of chronic diseases, including metabolic syndrome, has been suggested from several epidemiologic studies in which PA was shown to have a protective effect.…”
Section: Introductionmentioning
confidence: 99%